Implementasi Prudential Principle yang Diterapkan oleh Notaris dalam Penerimaan Uang Titipan BPHTB dan Uang Pemisah Sertifikat - Kenzodhy Armando Syahputra; R. Rahaditya (Syntax Corporation, 2023)
This research explores the implementation of the prudence principle by notaries in handling land certificate separation fees and BPHTB payments. As public officials, notaries play a crucial role in providing legal certainty and protection to the public. In executing their duties, notaries must maintain integrity and public trust by adhering to UUJN (Notary Law) and PMPJ (Principle of Recognizing Service Users). The study employs a juridical-normative method with legal and case-based approaches, conducting qualitative data analysis. In the acceptance of entrusted funds, notaries are required to ensure client identities, meticulously verify data, and maintain transparency and accountability. Although there is no explicit rule allowing notaries to accept BPHTB payments, some cases indicate notaries receiving funds from clients for these payments, albeit beyond their formal jurisdiction. Notarial responsibilities are based on the principle of error, encompassing actions, elements of fault, losses, and causality. Notarial errors can result in civil, administrative, and criminal liabilities. Therefore, the application of prudence, moral integrity, and compliance with the law are pivotal in preserving notarial responsibilities and public trust in the profession. This study emphasizes the importance of notaries adhering to prudence, understanding their boundaries, and facing legal accountability. Strict supervision and stringent penalties are necessary to raise awareness and deter notarial misconduct. Regulations concerning the notary's role in tax payments need reassessment, and the public should be educated about BPHTB payments to prevent issues with notaries. These measures are anticipated to enhance notarial integrity, public confidence, and legal certainty in Indonesia.